KEBIJAKAN PENGEMBANGAN SUMBER DAYA MANUSIA DI KOTA KEDIRI DALAM RANGKA PENINGKATAN INDEK PEMBANGUNAN MANUSIA - Suwarno Suwarno; Teguh Pramono (Optimum: Jurnal Ekonomi dan Pembangunan, 2020)
The purpose of this study is to explore the relationship between human resource development in order to improve the 2014-2018 human development index in Kadiri City. Previous studies state that there is no significant relationship between economic growth and the process of human development. Economic growth does not contribute to human development. However, this is not the case in Kediri City. By using descriptive research methods documentation and literature. Data obtained using the method of documentation from formal government sources that have been published so that it can be categorized as valid and responsive data. The analysis was carried out by describing human resource development policies in terms of education, health, income level, employment, and other aspects that could increase the human development index (HDI) in Kediri City. Based on the results of the study revealed that the human resource development policy in the City of Kediri in the context of increasing the human development index (HDI) has been going very well, it is proven, the HDI of the City of Kediri for the last five years has always been above the East Java and National average. The success of the City of Kediri in increasing the HDI is due to the seriousness of the local government in increasing participation rates and the level of public education. Local governments are also serious in improving public health. In addition, the city government of Kediri also increased community income, poverty alleviation, increased GRDP, and various other businesses that were simultaneous and continued to manage. Furthermore, new findings from this study can contribute to stakeholders in taking strategic policy steps and suggesting that local governments increase the human development index (HDI) in their region by encouraging the development of human resources.